Analisis Debit Air dan Parameter Fisika Air sebagai Dasar Perencanaan Irigasi Namu Ukur-Nambiki Kabupaten Langkat - Melky Aprianto Basardo Purba; Andreas Franskivo Marbun; Amanda Pratiwi Lubis; Rizky Simanjuntak (Politeknik Negeri Lhokseumawe, 2026)
Abstract — This research was conducted at the Namu Ukur–Nambiki Secondary Irrigation Channel located in Sei Bingai District, Langkat Regency, with the aim of analyzing water discharge and physical water parameters in the irrigation channel. The study was carried out to identify flow conditions and the relationship between channel dimensions and water discharge. The research method used was field observation through direct measurements of flow velocity, channel width, and water depth at several observation segments. The collected data were analyzed to determine water discharge and the physical condition of water in the irrigation channel. The results indicated that flow velocity and water discharge in each segment varied due to differences in channel cross-sections, sedimentation, and vegetation around the channel. Overall, the channel condition was still adequate to support agricultural irrigation Keywords: Water Discharge, Irrigation Channel, Flow Velocity, Physical Water Parameters, Open Channel Hydraulics